2022
DOI: 10.1021/acsomega.2c02704
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of Xanthoxyline and Related Small Methyl Ketone Herbicides

Abstract: Xanthoxyline ( 1 ), a small natural methyl ketone, was previously reported as a plant growth inhibitor. In this research, related methyl ketones bearing electron-donating and electron-withdrawing groups, together with heteroaromatics, were investigated against seed germination and seedling growth of Chinese amaranth ( Amaranthus tricolor L. ) and barnyard grass [ Echinochloa crus-galli (L.) Beauv ]. The structure–activity relationships (SARs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
0
17
0
3
Order By: Relevance
“…Alston. In the study [ 230 ], related methyl ketones carrying electron-donor and acceptor groups or heterocyclic substituents were investigated as the inhibitors of seed germination and growth of seedlings of Amaranthus tricolor L. and E. crus-galli . On the SAR basis, the types and positions of substituents that are crucial for the activity of methyl ketone herbicides were established.…”
Section: Natural Phytotoxins As Prototypes Of Synthetic Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alston. In the study [ 230 ], related methyl ketones carrying electron-donor and acceptor groups or heterocyclic substituents were investigated as the inhibitors of seed germination and growth of seedlings of Amaranthus tricolor L. and E. crus-galli . On the SAR basis, the types and positions of substituents that are crucial for the activity of methyl ketone herbicides were established.…”
Section: Natural Phytotoxins As Prototypes Of Synthetic Herbicidesmentioning
confidence: 99%
“…It was found that indole derivatives, namely 3-acetylindole and 3-acetyl-7-azaindole, are the most active methyl ketones that strongly inhibit plant growth at low concentrations. The molecular docking results indicated the carbonyl, aromatic, and azaindole groups to be important for the interaction of the selected methyl ketones with plant HPPD [ 230 ].…”
Section: Natural Phytotoxins As Prototypes Of Synthetic Herbicidesmentioning
confidence: 99%
“…Furthermore, xanthoxyline showed a significant inhibitory effect on seed germination (15%) and inhibited the root growth (63%) of this annual grassy weed. However, acetophenone ( 1 ) and most of its para -monosubstituted derivatives 12 and 18 – 24 showed weak activity at a concentration of 400 μM on barnyard grass and Chinese amaranth ( Amaranthus tricolor L.) [ 102 ]. Regarding the ortho -monosubstituted acetophenone series, there is little information on its biological properties; however, the remarkable and specific seed germination inhibition effect (~75%, Chinese amaranth) of o -nitroacetophenone ( 25 ) allows us to consider it for the molecular design of new acetophenones that are active against weeds.…”
Section: Natural and Synthetic Closely Related Acetophenone Cousins A...mentioning
confidence: 99%
“…Regarding the ortho -monosubstituted acetophenone series, there is little information on its biological properties; however, the remarkable and specific seed germination inhibition effect (~75%, Chinese amaranth) of o -nitroacetophenone ( 25 ) allows us to consider it for the molecular design of new acetophenones that are active against weeds. Notably, molecular docking on the 4-hydroxyphenylpyruvate dioxygenase (HPPD) enzyme indicated that these acetophenone derivatives may be involved in key interactions of HPPD inhibitors [ 102 ]. This finding is useful for developing small ketone herbicides.…”
Section: Natural and Synthetic Closely Related Acetophenone Cousins A...mentioning
confidence: 99%
“…The introduction of the methyl ketone structure at the indole 3-position of compound 24 ( Figure 5 ) produced a considerable inhibition of germination and shoot growth of the seeds of Amaranthus tricolor ( Chotpatiwetchkul et al., 2022 ). At a concentration of 400-800 μM, the germination of seeds was completely inhibited.…”
Section: Plant Growth Restrainersmentioning
confidence: 99%